Incremental prognostic value of tricuspid annular dilatation over the STS score. (25th November 2020) - Deseive, S; Steffen, J; Beckmann, M; Mehilli, J; Theiss, H; Braun, D; Hagl, C; Massberg, S; Hausleiter, J
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is the treatment of choice in most patients with severe aortic stenosis. The Society of Thoracic Surgeons (STS) score is a well established risk score to estimate morbidity, mortality and procedural risk of patients undergoing TAVR. However, tricuspid annular Dilatation (TAD), which is an increasingly recognized pathology associated with increased mortality, is not implemented in the STS Score. Purpose: The purpose of this analysis was to investigate the incremental prognoctic value of TAD over the STS score. Methods: Maximal septo-lateral diameter of the tricuspid annulus was measured in 923 patients on 3-dimensional MDCT datasets. A cut-off of 23 mm/m 2 body-surface area was revealed by receiver-operating curve statistics and used to define TAD. Incremental prognostic Information was tested with c-index statistics and continuous net reclassification improvement (NRI). Patients were followed for 2 years and all-cause mortality was defined as study endpoint. Results: Of 923 patients included in this analyis, TAD was found in 370 patients (40%). Patients with TAD had a significantly higher mortality (hazard ratio 2.18 with 95% CI 1.71 and 2.78, p<0.001). The mean STS score in the investigated patient cohort was 5.6±5.0. TAD provided incremental prognostic Information over the STS score when assessed with c-index statistics (rise from 0.63 to 0.66, p<0.01) or continuous NRI (0.209 with 95% CI 0.127 and 0.292, p<0.001). Estimated survival rates at 2 years were 88.2% (95% CI 84.5 and 92.1) in patients with a low STS score (<4) and no TAD and 57.5% (95% CI 51.1 and 64.7) in patients with a high STS score (>4) and TAD. Estimated survival rates in patients with a low STS score and TAD and patients with a high STS score and no TAD were similiar (75.8% with 95% CI 68.9 and 83.5 and 74.8% with 95% CI 69.2 and 80.7, respectively). Kaplan-Meier curves are shown in Figure 1. Conclusion: TAD is a common entity in patients undergoing TAVR for severe aortic stenosis. It is associated with significantly higher mortality and provides incremental prognostic Information over the STS score. Funding Acknowledgement: Type of funding source: None